2022
DOI: 10.3390/agronomy12112730
|View full text |Cite
|
Sign up to set email alerts
|

Vine Pruning-Derived Biochar for Agronomic Benefits

Abstract: The agronomic benefits of biochar (BC) prepared by slow pyrolysis of vine pruning residues, which are produced in large quantities in Romania, were evaluated. Three soil types, i.e., slightly alkaline fluvisol (S1), slightly acidic chernozem (S2), and strongly acidic luvisol (S3), with mean values of pH of 7.99, 6.26, and 5.40, were amended with BC at a volumetric ratio between BC and soil of 20/80. A greenhouse experiment was performed for 109 days to assess the effects of BC amendment on bell pepper growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This lack of significant differences in soil water retention capacity at explored h among the treatments contrasts with some expectations based on previous research indicating potential benefits of organic amendments on soil properties. For instance, other studies reported that the addition of organic amendments determines a reduction in the bulk density and an increase in the water retention capacity in the entire potential range considered [58,73,[75][76][77][78][79][80][81], with effects varying as a function of soil textural composition, application rates, incorporation depth, and amendment characteristics, and with more marked effects observed in sandy soils [73,78]. In addition, an increase in the micropores (diameter of 5-30 µm), playing an important role in retaining soil water [82,83]; and the larger specific surface area of the biochar, providing more adsorption sites for soil water, were reported to improve the water content of soils amended with biochar [80].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of significant differences in soil water retention capacity at explored h among the treatments contrasts with some expectations based on previous research indicating potential benefits of organic amendments on soil properties. For instance, other studies reported that the addition of organic amendments determines a reduction in the bulk density and an increase in the water retention capacity in the entire potential range considered [58,73,[75][76][77][78][79][80][81], with effects varying as a function of soil textural composition, application rates, incorporation depth, and amendment characteristics, and with more marked effects observed in sandy soils [73,78]. In addition, an increase in the micropores (diameter of 5-30 µm), playing an important role in retaining soil water [82,83]; and the larger specific surface area of the biochar, providing more adsorption sites for soil water, were reported to improve the water content of soils amended with biochar [80].…”
Section: Discussionmentioning
confidence: 99%
“…One-way ANOVA with Tukey's HSD post hoc test was applied to evaluate whether the process factors had a significant effect (p < 0.05) on dependent variables in terms of TPC, TAC, AC, and phenolic compound contents. The values of dependent variables obtained at different levels of extraction factors were processed using principal component analysis (PCA) [34][35][36]. The Pearson correlation coefficient (r) was used to evaluate the strength of linear correlations between dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, grapevine residues were converted to biochar [80,81]. However, few studies have assessed the effect of biochar application on soils used for cultivating grapevines.…”
Section: Discussionmentioning
confidence: 99%